(untitled) (Modern education and development, 2025)
The biochemical characteristics of the fetus in the late antenatal period largely determine the chemical composition and metabolic processes in the newborn’s body. Fetal metabolism and biochemical indicators are influenced by both processes occurring within the fetus itself and those taking place in the mother’s body, including the transport of metabolites through the placental barrier from the mother to the fetus.